The Application of MBSE to Inform Workforce Decision Making. Issue 1 (July 2017) - Bransden, Thomas; Do, Quoc; Farrell, Damien; Taylor, Stuart
Abstract: A novel application of Model Based Systems Engineering (MBSE) to a workforce context is presented. The DoDAF 2.02 metamodel (DM2) and associated architectural views are used to communicate key workforce information and relationships. This is implemented through a model‐centric system engineering methodology that ensures a common language, traceability, rationale and data integrity. Preliminary results indicate benefits to multiple stakeholders from organisational leaders to human resource professionals. Decisions relating to workforce design, development and realignment can be based on better understanding of interdependencies and traceability to organisational objectives.